(untitled) (Communications in Mathematical Research, 2021)
In this paper, we study one class of n-dimensional Hardy-Steklov operators which has important applications in the technical analysis in equity markets. We establish their weighted boundedness and the corresponding operator norms on both L^p (R^n) and BMO(R^n).